Analysis of Trace Metal Levels in Wild Mushrooms - Kaya, A.; Genccelep, H.; Uzun, Y.; Demirel, K. (Asian Journal of Chemistry, 2010)
Three macro elements and nine trace elements contents of 30 wild edible mushrooms collected from Kahramanmaras province of Turkey, were analyzed. The minimum and maximum heavy metal amounts of mushrooms were analyzed as mg/g dry weight for Ca (0.072-8.32), Mg (0.33- 6.56), K (8.11-28.15) and as mg/kg for Fe (65.56-7156), Zn (13.18-230.85), Cu (4.30-84.67), Cr (0.77-80.03), Mn (5.15-91.21), Pb (not detected-3.10), Ni (0.79-174.15), Cd (0.00-8.67) and Co (0.00-10.92). The potassium content was found to be higher than those of the other minerals in all mushrooms, studied and Morchella deliciosa was found to have the highest Fe, Cr, Mn, Pb, Ni and Co concentrations among the analyzed species.